The Difference of Morphological Mood and its Semantic Impact on Quranic Recitations: Amir Al-Shu'aby's Recitation as an Example - Rebat, Shaymaa Muhi; Kareem, Affan Khorsheed (International Journal of Psychosocial Rehabilitation, 2020)
The meanings of morphological structures change based on their mood. Each change of structure leads to a change in the meaning, which is clear in the Quranic recitations, and their roles of morphological structure difference that shows new indications and meanings. The study aims to relate morphological lecture to the noble Quran science by showing the difference of morphological structure in the imam (Amir Al- Shua'by's) recitation. The inductive deductive approach is employed based on the study resources and references to highlight some examples of imam (Amir Al- Shua'by's, dead 104 A.H) recitations, which falls within our competence. The reference here is to the difference of the morphological structure for the same word in that recitation and its effects on creating new meanings. The difference of meanings of the same word is one of the features of our blessed language to reveal some secrets of revelations and help understanding some meanings of the miraculous noble Quran including legitimate judgments that we cannot get through one recitation. The study has come to certain results including: the difference of nouns and verbs structures in the recitation of (Amir Al-Shu'aby) has its effect on meaning, and he agrees with other reciters on morphological mood and disagrees on others as Allah, the Almighty say: (Master of the Day of Judgment). This difference has created new meanings to control some legitimate judgments as Allah, the Almighty say: (Today all good things are made lawful for you. And the food of those given the Scripture is lawful for you, and your food is lawful for them. So are chaste believing women, and chaste women from the people who were given the Scripture before you, provided you give them their dowries, and take them in marriage, not in adultery, nor as mistresses. But whoever rejects faith, his work will be in vain, and in the Hereafter he will be among the losers) especially the recitation of (chaste women) as seen in the study.